2018
DOI: 10.1016/j.biortech.2018.03.120
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the integration of forward osmosis and anaerobic digestion for simultaneous wastewater treatment and resource recovery

Abstract: This study assessed the performance and key challenges associated with the integration of forward osmosis (FO) and anaerobic digestion for wastewater treatment and resource recovery. Using a thin film composite polyamide FO membrane, maximising the pre-concentration factor (i.e. system water recovery) resulted in the enrichment of organics and salinity in wastewater. Biomethane potential evaluation indicated that methane production increased correspondingly with the FO pre-concentration factor due to the organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 27 publications
(26 reference statements)
1
17
0
Order By: Relevance
“…20 g L À1 . Ansari et al [91] studied the effects of NaCl on anaerobic treatment of concentrated wastewater effluents in batch mode experiments and observed that by increasing water recovery rates of FO (from 50 to 90%), the anaerobic process achieves higher methane production (approximately 5 times higher), while the presence of salinity has a negligible negative effect.…”
Section: Salinity the Greatest Impact Of Fo On Anaerobic Treatmentmentioning
confidence: 99%
“…20 g L À1 . Ansari et al [91] studied the effects of NaCl on anaerobic treatment of concentrated wastewater effluents in batch mode experiments and observed that by increasing water recovery rates of FO (from 50 to 90%), the anaerobic process achieves higher methane production (approximately 5 times higher), while the presence of salinity has a negligible negative effect.…”
Section: Salinity the Greatest Impact Of Fo On Anaerobic Treatmentmentioning
confidence: 99%
“…The pre-concentration of low strength WW by FO when combined with anaerobic digestion, has several benefits, including higher biogas production, recovery of nutrients, lower FO membrane fouling propensity and smaller digester volume [ 111 ]. A large numbers of studies has been recently published relating the interests, limitations and optimisations of such schemes [ 124 , 125 ]. Several studies have already tried to implement FO for pre concentrating WW for subsequent treatment via anaerobic digestion.…”
Section: Applications Of Fo As Concentrating Processmentioning
confidence: 99%
“…However, in this study, the three different recovery scenarios (i.e. 50, 80 and 90%) were selected since (i) high FO recoveries (≥50%) can enhance the operability and applicability of AnMBR technology and (ii) FO recoveries up to 90% have been achieved for municipal wastewater pre-concentration (Ansari et al, 2018).…”
Section: Evaluated Wastewater Treatment Scenarios and Design Criteriamentioning
confidence: 99%